Spectrophotometric Determination of Cefotaxime via Diazotization Reaction in Pure and Pharmaceutical Samples - Abbas, Sumayha Mohammed; Mohammed, Mohammed Najah (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
An accurate and sensitive spectrophotometric method has been developed for the determination of cefotaxime (CEF) in pure and pharmaceutical samples. The suggested method depended on the coupling reaction between diazotized cefotaxime and 3,5-dimethyl phenol (3,5-DMPH) in basic medium to form light orange, water soluble dye, that is stable and has a maximum absorbance at 497nm. The calibration graph was liner over the concentration range (1-70) µg.mL-1 with LOD of 0.750 µg.mL-1 and LOQ of. 2.740 µg. mL-1, sandal sensitivity of 0.0526 µg. cm-2 . molar absorptivity 11328 Lmol-1 cm-1 . The stoichiometry composition was found by Jobs and mole ratio methods to the formation dye (1:1). The suggested method has been applied successfully to the determination of CEF in pure and pharmaceutical synthetic sample.